A CLASSIFICATION OF TABOO: FOCUSING ON SOCIOCULTURAL AND RELIGIOUS CATEGORIES (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article analyzes the complexities of translating religious and sociocultural taboos from English literature into Uzbek. It highlights the conflict between explicit Western narratives and the conservative, Islamic-influenced norms of Uzbek culture, where literal translation often causes cultural offense. Drawing on functionalist translation theories (Vermeer, Nord, Pym), the study proposes strategies to reconcile these divides. The research aims to define translation norms that preserve the original text's communicative intent while ensuring the target text remains culturally acceptable to Uzbek readers.